Financial globalisation, financial inclusion and economic growth in Nigeria. An empirical outlook - Otapo, Toyin Waliu; Dare, David Funso; Ushie, Paul Obogo; Demehin, James Adeniyi (BOHR International Journal of Finance and Market Research, 2025)
In the context of financial globalization (FG), the promise of improved capital and technological inflow into developing economies to stimulate sustainable economic growth is soothing; however, the mediating effect of a deep, effective, and robust financial system needs to be investigated. Thus, this research examined the influence of FG as moderated by financial inclusion on the growth of the Nigerian economy. Secondary data were chiefly sourced from the Central Bank of Nigeria (CBN) statistical bulletin, and it spanned the 1986 structural adjustment program period to 2022. Gross domestic product (GDP) was regressed on FG (total foreign assets and liabilities over GDP, external debt), financial inclusion (commercial banks credit to the private sector, commercial banks’ branches, rural bank deposits and rural bank loans), and a vector of control variables (money supply (MSLP) and interest rate (INT)). The generalized method of moments (GMM) was used for regression, and the Augmented Dickey Fuller was used for unit root analysis. It was shown from the results that FG had a positive effect on economic growth in Nigeria, but the cheering promise of globalization was yet to be fully complimented by the domestic financial system, consequently, the present policy trajectory towards globalization and liberalization should be sustained while the domestic financial system should be strengthened to expand its reach, products, and intermediation capabilities.